Assessment of Digitalization in Higher Education: A Case Study of Turan University - Orazbek, Y.; Davletova, M.T.; Dulatbekova, N.S. (BUKETOV BUSINESS REVIEW, 2024)
Object: This study evaluates the impact of digitalization on the operational performance, teaching, learning out comes, and student experiences at Turan University. Methods: Employing a mixed-methods approach, the research utilized a comprehensive questionnaire distributed to 86 students, alongside interviews with faculty to gauge the effectiveness of digital tools and platforms implemented across the university. Findings: The analysis reveals a generally positive perception of digital infrastructure and educational practices among students. High levels of satisfaction were noted in areas such as the availability of digital resources in the library and the use of digital technologies by teachers. However, variations in satisfaction regarding accessibility to necessary digital devices and the cost implications of digital tools indicate areas needing improvement. Conclusion: While Turan University has made significant strides in integrating digital technologies, the study identifies critical gaps in technological accessibility and financial aspects of digital usage. Addressing these gaps is es sential for enhancing the overall effectiveness of digitalization efforts and ensuring equitable access to digital resources for all students.